Cost-effectiveness of switching from trivalent to quadrivalent inactivated influenza vaccines for the at-risk population in Italy - Francesco Saverio Mennini; Chiara Bini; Andrea Marcellusi; Alessandro Rinaldi; Elisabetta Franco (Taylor & Francis Group, 2018)
Seasonal influenza is caused by two subtypes of influenza A and two lineages of influenza B. Although trivalent influenza vaccines (TIVs) contain both circulating A strains, they contain only a single B-lineage strain. This can lead to mismatches between the vaccine and predominant circulating B lineages, a concern especially for at-risk populations. Quadrivalent influenza vaccines (QIVs) containing a strain from both B lineages have been developed to improve protection against influenza. Here, we used a cost-utility model to examine whether switching from TIV to QIV would be cost-effective for the at-risk population in Italy. Costs were estimated from the payer and societal perspectives. The discount rate for outcomes was 3.0%. Univariate and probabilistic sensitivity analyses were performed to examine the effects of variations in parameters. Switching from TIV to QIV in Italy was estimated to increase quality-adjusted life-years (QALYs) and produce cost savings, including €1.6 million for hospitalization and approximately €2 million in productivity. The incremental cost-effectiveness ratio was €23,426 per QALY from a payer perspective and €21,096 per QALY from a societal perspective. Switching to QIV was most cost-effective for individuals ≥ 65 years of age (€19,170 per QALY). Probabilistic sensitivity analysis showed that the switching from TIV to QIV would be cost-effective for > 91% of simulation at a maximum willingness-to-pay threshold of €40,000 per QALY gained. Although the model did not take herd protection into account, it predicted that the switch from TIV to QIV would be cost-effective for the at-risk population in Italy.